2015
DOI: 10.1002/open.201500096
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Precise Quantification of Iron Catalyst Content in Carbon Nanotubes Using UV/Visible Spectroscopy

Abstract: Iron catalysts have been used widely for the mass production of carbon nanotubes (CNTs) with high yield. In this study, UV/visible spectroscopy was used to determine the Fe catalyst content in CNTs using a colorimetric technique. Fe ions in solution form red–orange complexes with 1,10-phenanthroline, producing an absorption peak at λ=510 nm, the intensity of which is proportional to the solution Fe concentration. A series of standard Fe solutions were formulated to establish the relationship between optical ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
(91 reference statements)
3
15
0
Order By: Relevance
“…Compared to a solution of the molecular iron(II) complex [Fe(phen) 3 ]SO 4 , depicting a characteristic three shouldered trace with a maximum at 507 nm, the trace of Fe II ‐SCNPs exhibits a similar shape with a maximum resonance at 512 nm (Figure ). Similar trace shape and literature references validate the assumption of a 3:1 ligand to metal ratio complex formation as the resulting folding unit of the Fe II ‐SCNPs . In comparison, [Ni(phen) 3 ]SO 4 does not exhibit an intense color.…”
Section: Resultssupporting
confidence: 84%
“…Compared to a solution of the molecular iron(II) complex [Fe(phen) 3 ]SO 4 , depicting a characteristic three shouldered trace with a maximum at 507 nm, the trace of Fe II ‐SCNPs exhibits a similar shape with a maximum resonance at 512 nm (Figure ). Similar trace shape and literature references validate the assumption of a 3:1 ligand to metal ratio complex formation as the resulting folding unit of the Fe II ‐SCNPs . In comparison, [Ni(phen) 3 ]SO 4 does not exhibit an intense color.…”
Section: Resultssupporting
confidence: 84%
“…We quantified the Fe 2+ bound to FXN after desalting by using a colorimetric assay [50], and determined the Fe 2+ content to be 0.92 ± 0.15 mol Fe 2+ /mol FXN. Comparison of the 1 H, 15 N TROSY-HSQC spectrum of [U- 15 N]-FXN, without and with bound Fe 2+ , revealed that iron binding led to shifts of peaks from residues D112, L113, and D115 and the disappearance of peaks from residues V125, S126, and F127 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fe 2+ was quantified by a colorimetric assay as described previously [50]. 200 μL of 12 M HCl was added to 20 μL of 0.26 mM Fe 2+ -FXN after desalting.…”
Section: Methodsmentioning
confidence: 99%
“…Even though wipe sampling may be considered qualitative, an analytical method is needed that includes an efficient digestion step and adequate detection limits to ensure reliable and reproducible metal determinations. The most commonly used analytical methods for determining metal impurities in CNTs are Neutron Activation Analysis (NAA) [1, 3, 2022], Direct Solid Sampling Electrothermal Atomic Absorption Spectrometry (DSS-ET AAS) [21], High Resolution Continuum Source Graphite Furnace Atomic Absorption Spectrometry (HR CS GFAAS) [9], Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) [1, 4, 20, 21, 23, 24], and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) [1, 3, 4, 7, 20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…The key challenge is the difficulty in quantitatively extracting CNT metal impurities during the digestion step [3, 4, 7, 22, 26]. A variety of sample pretreatments have been employed for determination of metals in CNT samples including wet digestion [1, 3, 23], dry ashing combined with acid digestion [1, 3, 4], Carius tube digestion [22], microwave-assisted acid digestion [1, 3, 4, 20, 26], and microwave-induced combustion [4, 21, 24]. Grinberg and coworkers [4] reported incomplete recovery of metals from CNTs with the single-step microwave digestion (HNO 3 and H 2 O 2 ) recommended by Decker et al [26] and proposed a multistep microwave-assisted procedure that involved the repeated use of strong acids as follows: HNO 3 combined with H 2 O 2 (1x), HNO 3 alone (3x), evaporation near dryness, HNO 3 and HClO 4 followed by HNO 3 addition and evaporation to dryness (4x), and finally dissolution and dilution in 1% HNO 3 .…”
Section: Introductionmentioning
confidence: 99%